Experience of exclusion: A framework analysis of socioeconomic factors affecting cardiac rehabilitation participation among patients with acute coronary syndrome. (December 2017) - Pedersen, Maria; Overgaard, Dorthe; Andersen, Ingelise; Baastrup, Marie; Egerod, Ingrid
Background: The Danish public healthcare system provides comprehensive care based on the principle of equal access. However, it is well documented that patients with low socioeconomic position are less likely to participate in cardiac rehabilitation. More knowledge is needed to understand this phenomenon. The aim of the study was to explore the patient experience of barriers to completion of phase II cardiac rehabilitation, and to investigate the impact of socioeconomic factors on completion of cardiac rehabilitation. Methods: The study had a qualitative explorative design using semi-structured individual or dyadic interviews with patients ( n = 24) and close relatives ( n = 12). Informants were sampled from a quantitative prospective study of 302 patients with acute coronary syndrome and data were analyzed using the framework method. Results: Patients in different socioeconomic groups were challenged by a rigid and non-individualized rehabilitation program. A total of five themes were identified that might explain non-participation in cardiac rehabilitation: exclusion by time and place, exclusion by health beliefs, exclusion from counseling, exclusion by alienation, and exclusion of relatives. The themes were described in a matrix of socioeconomic factors of age, sex, education and employment. Conclusions: Patients in various socioeconomic subgroups felt excluded from cardiac rehabilitation for different reasons. This study supports earlier findings and provides examples of real-life issues that need to be addressed to prevent attrition and encourage participation. Equal access to cardiac rehabilitation can only be reached if the physical and psychological needs of patient and family are met by tailoring therapy to consider age, sex, education and employment groups.